Legal Responsibility of Chartered Accountant - Mohammed Hassan , Lect. Jasim; Omeer Saaki , Assist. Lect. Elhaam (Basra studies journal, 2024)
The study seeks to shed light on the administrative and legal responsibility to which the chartered accountant is subject when carrying out the duties specified for the accountant under the law, like those related to auditing the financial statements and revealing cases of misleading and fundamental errors that may be included in those statements, and what the laws and instructions require of accountants to enjoy neutrality and independence in preparing and issuing the final report and what it includes in terms of transparency in addressing all financial and other violations, which may lead to the spread of the phenomenon of financial and administrative corruption. The responsibility of the chartered accountant is mainly focused on confronting and providing a type of preventive protection against a number of risks in the financial statements, which can be embodied in all errors and fraud cases that can be included in those statements, whether intentional or unintentional, and what this requires of him performing his duties by informing the management of all those violations and errors. Otherwise, he is exposed to the following responsibilities: First: Criminal liability resulting from his violation of the provisions of various penal legislations. Second: Administrative liability resulting from his breach of the rules of professional conduct and duties. In addition, the study concluded that the responsibility also falls on the beneficiary party as it is primarily responsible for providing a coherent and sound internal control system, and taking into account its application in a fundamental manner; because this reduces the possibility of the existence and spread of cases of deception and error in the financial statements, which is positively reflected in addressing cases of administrative and financial corruption in all its forms and manifestations